2022
DOI: 10.4102/sajip.v48i0.1964
|View full text |Cite
|
Sign up to set email alerts
|

Employee engagement of special needs teachers in Windhoek, Namibia: The moderating role of job crafting

Abstract: Orientation: Learners with disabilities can acquire from special education schools the basic knowledge and skills to enable participation in various economic and social activities. The engagement of special needs teachers is pivotal in this regard.Research purpose: To identify the work factors that are most salient in accounting for variance in the engagement of special needs teachers in Windhoek, Namibia. To test the effects of job crafting on the relationship between identified work factors and employee enga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Moreover, SETs in these JD-R profiles (compared to demanding and poor jobs) experienced lower emotional demands. Although Minghui et al (2018) , Murangi and Bailey (2022) conducted variable-oriented (rather than person-oriented) studies, their findings showed that job demands and resources (e.g., autonomy, colleague support and rewards, and recognition) were associated with work engagement.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, SETs in these JD-R profiles (compared to demanding and poor jobs) experienced lower emotional demands. Although Minghui et al (2018) , Murangi and Bailey (2022) conducted variable-oriented (rather than person-oriented) studies, their findings showed that job demands and resources (e.g., autonomy, colleague support and rewards, and recognition) were associated with work engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Minghui et al (2018) showed that social support is a critical job resource for SETs. In Namibia, job resources, including autonomy, co-worker support, and rewards and recognition, showed moderate relationships with the work engagement of SETs (Murangi and Bailey, 2022). Billingsley and Bettini (2019) found that SETs' perceptions of job demands increased their intentions to leave, especially when these demands exceed their capacity to fulfill them.…”
Section: Job Demands and Resourcesmentioning
confidence: 97%
See 3 more Smart Citations